Tax Incidence and Tax Avoidance* - Dyreng, Scott D.; Jacob, Martin; Jiang, Xu; Müller, Maximilian A. (Contemporary Accounting Research, 2022)
ABSTRACT Economists broadly agree that the economic burden of corporate taxes is not entirely borne by shareholders but also borne in part by employees and consumers. We examine corporate tax avoidance in a setting where shareholders do not bear the entire economic burden of the corporate tax. We show that the relation between corporate tax incidence and corporate tax avoidance depends on the elasticity of labor supply, the productivity of capital relative to labor, and the tax deductibility of labor and capital. These forces operate through two channels ( firm scale and input mix ), making the actual association between tax avoidance and incidence an empirical question. We find that firms whose shareholders bear less of the economic burden of corporate taxes engage in less avoidance. Our findings suggest that maximizing after‐tax profits might entail less tax avoidance if shareholders do not entirely bear the corporate tax burden. In particular, when the incidence of the corporate tax falls on the firm, firms avoid more taxes. This tendency is stronger if firms use a higher level of capital input, if the deductibility of the cost of capital investment is limited, if firms have high capital productivity, or if tax enforcement is strong.